2012
DOI: 10.1016/j.sse.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

PNP PIN bipolar phototransistors for high-speed applications built in a 180nm CMOS process

Abstract: Highlights► Three speed optimized pnp phototransistors built in a 180 nm CMOS process are shown. ► A thick low doped intrinsic layer was implemented between base and collector. ► A thick base–collector space-charge region leads to high bandwidths. ► Optical characterisations were done at 410 nm, 675 nm and 850 nm. ► Bandwidths up to 76.9 MHz and dynamic responsivities up to 2.89 A/W were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The measured photoresponsivity decreases with increasing optical power. This phenomenon is typically observed in phototransistors due to high light power affecting the gate and/or base potential 11 12 . We found that the decrease of ON with increasing P IN can be fitted by a power law of the form: ON ∝ P IN β with β values between −0.7 – −0.9 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured photoresponsivity decreases with increasing optical power. This phenomenon is typically observed in phototransistors due to high light power affecting the gate and/or base potential 11 12 . We found that the decrease of ON with increasing P IN can be fitted by a power law of the form: ON ∝ P IN β with β values between −0.7 – −0.9 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using a phototransistor (PT) that is a photodetector with internal gain may help mitigate these issues. In fact, several attempts have been made in the design and fabrication of phototransistors with different device configurations including MOSFETs 6 7 , JFETs 8 9 , and BJTs 10 11 12 . A photoMOSFET in a standard MOS configuration that eliminates metal wires connecting photodiodes and their proximal MOSFETs in receiver circuits is the most promising solution to simultaneously realize photodetection and electrical amplification within a single device.…”
mentioning
confidence: 99%
“…Theoretically, even when the base of the NPN phototransistor is not connected and wired, the light sensitivity of a phototransistor still outperform a photodiode by providing an additional gain in the case of low light detection [21]. Therefore, using phototransistor as primary device becomes the preferred choice for low intensity light detection in low turbidity situations.…”
Section: > Replace This Line With Your Paper Identification Number (Dmentioning
confidence: 99%
“…The used PTs (50 B Center E , 100 B Edge E and 100 B Quad E ) are presented in [5]. The cross section of one PT (50 B Center E ) is depicted in Fig.…”
Section: A Phototransistorsmentioning
confidence: 99%